Evaluation of novel propellants manufactured from commercially available Thermoplastic Elastomers (TPE) using resonant acoustic mixing - Wilkinson, Peter John (Cranfield University, 2019)
The key issues in developing a sustainable gun or rocket propellants are financial, environmental, legislative and safety. Use of commercially available off the shelf polymers, in particular, thermoplastic elastomers (TPE) as a binder for propellants could address these issues. The propellant would need to have suitable mechanical and thermal properties, as well as, adequate ballistic performance. Traditional manufacture techniques for propellant are not suitable for TPE binders and so new mixing and manufacturing techniques will be investigated. A literature review is presented detailing conventional propellants, low vulnerability (LOVA) propellants and research into using TPEs as binders for propellants. In addition, the desirable mechanical and ballistic properties of propellants are assessed. The TPEs PEBAX, a polyether-block-amide (PEBA) and SEBS, a Styreneethylene/butylene-styrene were selected for analysis. A full assessment of the mechanical and thermal properties of these TPEs was conducted. They both have broadly suitable properties, however, both TPEs were substantially stiffer (greater storage modulus) than a typical binder and the lower glass transition for SEBS was above the desired minimum operational temperature. When plasticised with Dioctyl Sebacate (DOS), both PEBAX and SEBS had a reduction in the storage modulus and lower glass transition. PEBAX did not show any noticeable effect on the upper (melt) transition, conversely SEBS showed a larger reduction in the upper (glass) transition. SEBS was down selected for further evaluation due to its better availability, purity and greater solubility in solvents. Traditional mixing and manufacturing techniques where not suitable for processing of propellants with TPE binders. Slurry processing (used in manufacture of pressed PBXs) was selected to coat the filler, creating a moulding powder. This was replicated with a novel method using resonant acoustic mixing (RAM). The moulding powder was then consolidated by remote hot pressing to simulate an industrial extrusion or rolling process. This process was used to successfully manufacture two propellants using SEBS as the binder, AP/SEBS containing ammonium perchlorate (AP) as a filler and RDX/SEBS with RDX. Inert fillers of sugar and talc were trialled, and mechanical testing of these inerts was found to be generally in good agreement with the live fills. ii Initial combustion work on RDX/SEBS by closed bomb analysis at low pressure was indicative of good burning, with a low burn rate. Both AP/SEBS and RDX/SEBS were subject to thermal and mechanical analysis. This showed that the glass transitions (Tg) were only slightly changed from pure SEBS. In comparison to AP-composite propellants, both the storage modulus (E’) from DMA and Young’s modulus (E0) from tensile testing were substantially greater. The maximum stress (σm) was similar, however the maximum extension (εb) was less. With further optimisation, such as use of bonding agents, plasticisers, optimised particle size and improve manufacturing methods, it is believed that the maximum extension could be increased. Therefore a SEBS based propellant should deform less to an applied force, but still have a similar extension and hence elasticity to hydroxyl-terminated polybutadiene (HTPB) composite propellants. These theoretical improved mechanical properties should result in a safer propellant. This research has increased the knowledge and understanding of propellants based on commercially available TPEs. It is anticipated that this will be valuable in developing sustainable propellants of the future.